ANALISIS HASIL BELAJAR MATEMATIKA DAN HASIL TRY-OUT UJIAN NASIONAL MATEMATIKA PESERTA DIDIK MADRASAH IBTIDAIYAH - Zainal, Nur Fitriani; Sahibe, Nurhayati; Satriani, Satriani (PD PGMI se Indonesia, 2021)
This study aims to describe the learning outcomes of Mathematics, the results of the Mathematics National Examination try-out, and test the significance of the differences between the Mathematic learning outcomes and the Mathematics National Examination try-out results. The research was conducted through a quantitative approach with a research population of 92 students of 6th-grade of MIN in Manado city. Research data were collected using documentation techniques and test techniques. Documentation of learning outcomes in the form of 5th-grade report cards for even semester Mathematics 2018/2019 and a test in the form of the Try-out of Mathematics National Examination (UN) which was carried out twice. The collected data were then analyzed descriptively and inferentially using the Wilcoxon test. The Wilcoxon test was used because the data on Mathematics learning outcomes were not normally distributed. From the results of the analysis, it has known that: 1) The category of students' mathematics learning outcomes is in the range of Very Good, Good and Sufficient predicates and if averaged, it is in the Enough predicate, 2) The Scores of the try-out of mathematic National Examination are in the less category and 3) there is a significant difference between the results of learning Mathematics and the results of the Try-Out of Mathematics National Examination (UN) of students. The results of this study can be used as reflective material for teachers in maximizing students' basic Mathematics skills which will have an impact on learning Mathematics at the next level and in preparing SD/MI students to face National and International assessments.